The defense repertoire of males of Leptodactylus vastus Lutz 1930 in a fragment of the Atlantic Forest in northeastern Brazil. Issue 3 (4th May 2023) - de Oliveira-Santos, José R.; Bressan Queiroz de Figueiredo, Regina C.; Barbosa de Moura, Geraldo J.
Abstract : Anurans present different defence mechanisms against predator attacks. There are more than 30 defence strategies that these animals can display in the different environments where they can be preyed upon. We analysed the defence repertoire of the species Leptodactylus vastus Lutz 1930, including the male distress call and its intra and interindividual coefficients of variation. We carried out this study in a fragment of Semideciduous Atlantic Forest at the Camocim Conservation Unit in the metropolitan region of Recife, Pernambuco, northeastern Brazil. The defensive displays of 30 males to different stimuli simulating a predator were analysed. We observed five types of strategies which were used by these animals separately or concomitantly: puffing up the body (100%), push movement (83.3%), distress call (33.3%), hiding (23.3%), cloacal discharge (16.6%) and spine aggression (6.6%). The analysis of intra and interindividual coefficient of variation showed that there was no acoustic variation in the distress call of this species. Understanding the defensive mechanisms of a species is important to identify the antipredatory strategies used by animals, especially in face of emerging threats, and to help to produce proposals for the conservation of neotropical species. Highlights: Studies on the defensive behaviour of anurans have been presented information that can help in the construction of the natural history of the species in this group. The results show that males of Leptodactylus vastus exhibited five types of defensive behaviours, of which 4 were of visual origin: puffing up the body, push, hiding, cloacal discharge, and spinal aggression; and one type of acoustic behaviour: distress call. The behaviours were observed through three types of external stimuli, in which during the data analysis it was evident that there is no male preference for a specific type of stimulus. Through the interindividual and interindividual coefficient of variation that there are no significant variations in the distress call, being an unprecedented result for works that involve the distress call.